ASSESSING THE IMPACT OF CLIMATE CHANGE ON RENEWABLE ENERGY SYSTEMS IN NIGERIA: A REVIEW - Umar, Nuhu; Agbele, Idowu Elijah; Adeagbo, Kehinde Olusoji (FUDMA Journal of Sciences, 2026)
Climate change poses significant environmental challenges, particularly in Nigeria, where the economy heavily relies on fossil fuels. This dependency has led to adverse effects, including increased wildfires, droughts, health impacts, and coastal flooding. The alteration in climate patterns is primarily attributed to both natural phenomena and human activities that change atmospheric compositions. The paper discusses the potential of renewable energy sources as a critical solution to mitigate climate change impacts. It reviews current energy sources in Nigeria and highlights the urgent need to transition towards renewable energy to reduce environmental harm and enhance energy security for sustainable development.